Growth and yield of irrigated maize (Zea mays L.) as influenced by mechanization and nutrient management practices - Sivamurugan, A P; Surendrakumar, A; Bharathi, C; Karthikeyan, R; Pazhanivelan, S; Manivannan, V; Shanmugapriya, P (Plant Science Today, 2025)
Maize is a dominant and promising crop grown in almost all regions throughout the year for various purposes, owing to its wide adaptability. In India, the productivity of maize is low, which can be attributed to usage of conventional varieties, inadequate supply of organic and inorganic fertilizers, low adoption of mechanization practices, and the indiscriminate use of pesticides and fungicides etc. Among these factors, mechanization and nutrient management practices play a critical role in influencing productivity through supply of nutrients and ensuring timeliness of operations. Keeping in view the above facts, field experiments were conducted in the Department of Agronomy and the Department of Millets during Kharif seasons of 2018, 2019 and 2020 to study the growth and yield of irrigated maize as influenced by mechanization practices and nutrient management strategies. The results of mechanization experiment revealed that T3 - sowing by inclined plate planter (75 × 20 cm – drip tape irrigation) + spraying of pre-emergence herbicide (3 days after sowing (DAS) - after irrigation) + weeding by power weeder (30 - 35 DAS) achieved higher grain yield (5549 kg ha-1), net returns (Rs. 58, 158 ha-1), and B:C ratio (2.66). The results of nutrient management experiments revealed that the application of 250:75:75 kg NPK/ha (100% the recommended dose of fertilizer (RDF) achieved higher grain yield (7327 kg ha-1), net returns (Rs. 73518/ha) and B: C ratio (2.50) in maize (T2).